2022
DOI: 10.2337/dc21-2136
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characteristics of Remission of Type 2 Diabetes in England: A Cohort Study Using the National Diabetes Audit

Abstract: OBJECTIVE To assess the incidence of remission of type 2 diabetes in routine care settings. RESEARCH DESIGN AND METHODS People with type 2 diabetes (HbA1c ≥48 mmol/mol (6.5%) or <48 mmol/mol (6.5%) with a prescription for glucose-lowering medications) alive on 1 April 2018 were identified from a national collation of health records in England and followed until 31 December 2019. Remission was defined as two HbA1c measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 17 publications
4
41
1
Order By: Relevance
“…16 In a previous analysis of the incidence of remission of type 2 diabetes using NDA data showed that short‐term relapse to diabetic hyperglycaemia was approximately 9% over a median of 190 days. 17 This highlights the importance of ongoing diabetes‐related care delivery to identify a potential relapse and future macro and microvascular risk for those achieving remission.…”
Section: Discussionmentioning
confidence: 99%
“…16 In a previous analysis of the incidence of remission of type 2 diabetes using NDA data showed that short‐term relapse to diabetic hyperglycaemia was approximately 9% over a median of 190 days. 17 This highlights the importance of ongoing diabetes‐related care delivery to identify a potential relapse and future macro and microvascular risk for those achieving remission.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have shown that weight loss ≥ 15% is necessary in the first years of T2D diagnosis to achieve disease remission [24,25]. Nevertheless, the incidence of T2D remission in routine care settings is infrequent (< 1%) [30], in particular in patients with depressive symptoms [31]. Indeed, depression favors weight gain and determines a 60% increased risk of developing T2D [32][33][34] directly through three of its symptoms that we have re-named Bridge Symptoms (BS): alteration of eating behavior [35,36], reduced physical activity [37,38] and inadequate sleep duration [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Performing psychiatric screening in patients with T2D is needed to intercept cases of mental disorder that might otherwise remain unknown and to intervene on the development of T2D and its remission, considering how CPDs favor its onset and maintenance [17,30,42]. This could help reduce the T2D epidemic, driving a reduction in Years of Life Lost (YLL) given that Diabetes is the 9th cause of death worldwide, and it is an important contributing cause to the first and second cause of death globally (ischemic heart disease and stroke).…”
Section: Discussionmentioning
confidence: 99%
“…We used the 10% cutoff because there is a sharp cut‐off in percentage of people achiving remission above and below this point. 15 , 16 Mixed‐effects ANOVAs with a random person‐effect were undertaken to assess the within‐subject effect of ‘time’ (baseline, 12 month, 24 month), the between‐subject effect of weight loss (<10% or ≥ 10%), and any interaction effects. Between weight loss group estimates (β), 95% CI and p‐ values were recorded for each variable.…”
Section: Methodsmentioning
confidence: 99%